A Social Norm Nudge to Save More: A Field Experiment at a Retail Bank - Robert A. J. Dur; Dimitry Fleming; Marten van Garderen; Max van Lent (Tinbergen Institute, 2019)
A large fraction of households have very little savings buffer and are therefore vulnerable to financial shocks. We examine whether a social norm nudge can stimulate such households to save more by running a small-scale survey experiment and a large-scale field experiment at a retail bank in the Netherlands. The survey experiment shows that a social norm nudge increases intended savings. In line with this, we find in our field experiment that households who are exposed to the social norm nudge click more often on a link to a personal webpage where they can start or adjust an automatic savings plan. However, analyzing detailed bank data, we find no treatment effect on actual savings, neither in the short run nor in the long run. Our null findings are quite precisely estimated.
Keywords: G40; C93; D14; 330; household savings; field experiment; nudges; social norms